“Pushkin dictionary” by G.A. Shengeli: The unpublished article by the author of the concordance of A.S. Pushkin’s poems - Nikolay Vasilyev (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The publication introduces into scientific circulation an article by G.A. Shengeli (1894 – 1956), dedicated to “Pushkin's Dictionary” prepared by him in the second half of the 1930s, which was conceived as a concordance of the classic’s poetry, but remained unpublished (the manuscript was most likely lost). Dated 1955 by the authors and written by Shengeli to notify writers and scholars about the goals, structure and informational possibilities of the “Pushkin Dictionary”, the article is still relevant, being one of the few concrete testimonies of the scientist’s intention to study Pushkin’s language and linguistic poetics. The text is published according to the typescript with the author’s corrections, preserved in the fund of the journal "Oktiabr’" in the Russian State Archives of Literature and Arts. In Shengeli’s article it is noted that the very idea of compiling a dictionary to the works by Pushkin as the creator of the Russian literary language arose long ago, but the lack of scientifically reliable Pushkin editions hindered the implementation of the plan. The compilers of the Pushkin Dictionary took as a basis the texts of the 1936 six-volume Collected Works, issued by the Goslitizdat, where, according to the scientist, this problem was generally overcome. Highlighting the explanatory dictionary and the concordance dictionary as two main types of works describing the linguistic features of one or another author, Shengeli argues the choice of concordance, presented in the form of a set of dictionaries, united by a common word index, for composing the corpus of Pushkin's poetic language.